PROSPEK PEMBELAJARAN DAN PENDIDIKAN AGAMA ISLAM DALAM KONTEKS ERA GLOBAL DAN MANAJEMEN PEMBIAYAANNYA - Halid, Ahmad (Al-Ashr : Jurnal Pendidikan dan Pembelajaran Dasar, 2024)
This article examines the interesting things about the prospects for Islamic religious learning and education in the context of the global era and its financing management. This research is a review of the literature that strengthens research data with the results of research conducted by education experts. The research model is qualitative. Meanwhile, the data analysis uses descriptive. The data collection method uses library documents. Checking the validity of the data uses the results of expert research by comparing it with the results of this research. so that this version of research will be found strongly. Then it will be sharpened with content analysis (content analysis). The results of the research are (1) Prospects for Islamic and Religious Education as Improving the Quality of National Education (2) Prospects for Islamic and Religious Education in Indonesia in the Era of Globalization, (3) Prospects for the Development of Imprint and Science and Technology in Madrasah Education in Indonesia (4) Prospects and The Existence of Islamic and Religious Education in the Future (5) Management of Religious and Religious Education Financing